2011
DOI: 10.3417/2009107
|View full text |Cite
|
Sign up to set email alerts
|

Fagopyrum wenchuanenseandFagopyrum qiangcai, Two New Species of Polygonaceae from Sichuan, China

Abstract: Province, China, are described and illustrated. lentum Moench based on its leafy base, triangular leaves, and terminal or axillary racemes. The new differs in its caespitose habit, the plants often with variable in length, and the capsules are ellipsoidtriangular or broadly ovoid-triangular, 3-3.5 X 2.5-3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Both distyly and homostyly have been noted in previous studies of Fagopyrum (Darwin, 1877; Ohnishi, 1989; Ohnishi and Matsuoka, 1996; Nishimoto et al, 2003; Liu et al, 2008; Shao et al, 2011), but quantification of the reproductive system involved only the large‐achene group of buckwheat that includes F. dibotrys (Chen et al, 2014) and F. esculentum (Samborska‐Ciania et al, 1989; Björkman, 1995; Cawoy et al, 2006), while floral traits in F. tataricum and the small‐achene group of buckwheat have not before been examined. Compared to six species in the small‐achene group, flowers of the large‐achene group were significantly larger (test of corolla diameter, Wald χ 2 = 873.…”
Section: Discussionmentioning
confidence: 64%
“…Both distyly and homostyly have been noted in previous studies of Fagopyrum (Darwin, 1877; Ohnishi, 1989; Ohnishi and Matsuoka, 1996; Nishimoto et al, 2003; Liu et al, 2008; Shao et al, 2011), but quantification of the reproductive system involved only the large‐achene group of buckwheat that includes F. dibotrys (Chen et al, 2014) and F. esculentum (Samborska‐Ciania et al, 1989; Björkman, 1995; Cawoy et al, 2006), while floral traits in F. tataricum and the small‐achene group of buckwheat have not before been examined. Compared to six species in the small‐achene group, flowers of the large‐achene group were significantly larger (test of corolla diameter, Wald χ 2 = 873.…”
Section: Discussionmentioning
confidence: 64%
“…odontopterum and F. gracilipes are tetraploid (2n = 4x = 32) (Tang et al 2010;Yang et al 2010). In this research, we found that F. wenchuanense, F. qiangcai and F. pugense are diploid (2n = 2x = 16) (Tang et al 2010;Shao et al 2011), F. crispatofolium is tetraploid (2n = 4x = 32), F. qiangcai has one pair of satellite RNAs, and F. crispatofolium also has one pair of satellite RNAs, but their satellite RNAs have different positions and numbers. The karyotypes of F. wenchuanense, F. crispatofolium and F. pugense are 1A type, but F. qiangcai is 2A type.…”
Section: Discussionmentioning
confidence: 86%
“…1a (Shao et al 2011). The somatic chromosomes of F. wenchuanense indicate that the species is diploid, with a chromosome number of 2n = 2x = 16, and all 16 chromosomes are metacentric with no satellites.…”
Section: Fagopyrum Wenchuanense J R Shaomentioning
confidence: 99%
See 1 more Smart Citation
“…F. qiangcai was found at Kaku village, Wenchuan, where F. pleioramosum and F. callianthum distribute (Shao et al 2011). F. qiangcai bears heterostylous flowers with pink perianths and sagittate leaves with red veins.…”
Section: Recent Discovery Of the New Species Of Fagopyrum And Their Smentioning
confidence: 99%